SYSTEMIC CORTICOSTEROIDS ASSOCIATED WITH INTRATYMPANIC CORTICOSTEROID TREATMENT FOR IDIOPATHIC SUDDEN HEARING LOSS - Bogdan Cavaleriu; Rădulescu Luminița; Dan Mârțu (Romanian Society of Oral Rehabilitation, 2013)
Objectives In this study we analyzed hearing recovery rates in patients diagnose with ISSHL after steroid treatment. We evaluate the therapeutic efficacy of intratympanic dexamethasone (ITD) injections added to systemic steroids(salvage therapy) in patients with idiopathic sudden sensorineural hearing loss (ISSNHL) and of ITD therapy as first line therapy. Methods A retrospective chart review was performed for patients diagnose with ISSNHL from last three years. Inclusion criteria define ISSNHL. Patients were treated with systemic corticoid therapy (Solu-medrol) and/or intratympanic therapy (Dexamethasone). Results Outcomes were analyzed as a function of the type of therapy, time to treatment and response. 68,8% of patients responded to treatment with steroid, while 42,22 % failed initial treatment with systemic steroid. 36,8 % of the nonresponders to systemic therapy, opted to receiving ITS salvage therapy. Conclusion Current findings recommend treating ISSNHL with both ITS and OS initially. In patient who do not tolerate OS, ITS should be attempted as first line therapy. ITS injections are an effective salvage therapy after failure with OS.